The Effect of Training On Employee Productivity at PT. Bima Sentosa Trikarya in Jakarta - Herjanto Subur; Sarwani Sarwani (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
This study aims to determine the effect of training on employee productivity at PT. Trikarya Bima Sentosa in Jakarta. The method used is explanatory research with a sample of 62 respondents. The analysis technique uses statistical analysis with regression, correlation, determination, and hypothesis testing. The results of this study of the training variable obtained an average score of 3.711 with suitable criteria. The employee productivity variable received an average score of 3.837 with applicable standards. Training has a positive and significant effect on employee productivity with a regression equation value of Y = 15,504 + 0.616X. A correlation coefficient value of 0.728 or has a strong relationship with a determination value of 53.0%. Hypothesis testing obtained a significance of 0.000 <0.05